355 Predictors of Longitudinal Sleep Outcomes in a Statewide Randomized Trial of Telephone Cognitive Behavioral Therapy for Insomnia. (3rd May 2021) - McCurry, Susan; Pike, Kenneth; Von Korff, Michael; Morin, Charles; Vitiello, Michael
Abstract: Introduction: We examined the relationship between treatment process measures and 12-month insomnia outcomes from a large clinical trial of telephone-delivered CBT-I. Methods: A statewide sample of 327 Kaiser Permanente Washington members aged 60+ with OA, Insomnia Severity Index (ISI) scores of 11+ and Brief Pain Inventory scores of 9+ were randomized to six sessions of individual telephone-delivered cognitive-behavior therapy for insomnia (CBT-I) vs. education-only control. Participants rated their perceptions of treatment credibility and perceived effectiveness on a 7-point Likert scale after session 1 and at 2-month post-test. They also completed the Sleep Hygiene Index (SHI), the 8-item Sleep Problem Acceptance Questionnaire (SPAQ), and the 8-item Chronic Pain Acceptance Questionnaire (CPAQ) at baseline, post-treatment, and 12 months. Insomnia outcome was measured using the ISI. Results: Participants (mean age=70.2 years [SD=6.81], 74.6% female, 87.8% with sleep problems for over 1 year) were randomized to the two treatment arms. Regression analyses controlling for baseline age, opioid use, depression, pain, and ISI showed that lower 12-month ISI scores were associated with CBT-I group membership and lower baseline ISI (both p<.001), higher session 1 ratings of treatment credibility (p=.004), higher baseline CPAQ activity engagement (AE) subscale scores (p=.04), and lower baseline SPAQ AE scores (p=.016) when predictors were simultaneously entered. Lower 12-month ISI scores were also associated with post-test ratings of treatment perceived effectiveness (p=.004) and higher SPAQ AE (p=.038) scores. Improvements on the SHI at post-test were significantly associated with lower 12-month ISI scores when variables were entered singly into regression models, but not when all predictors were entered simultaneously. SPAQ and CPAQ sleep and pain willingness subscale scores were not significantly related to ISI outcomes in any model. Conclusion: People with less severe baseline insomnia levels who received telephone-delivered CBT-I were more likely to have lower 12-month ISI scores. Participant perceptions of treatment credibility and effectiveness, and engagement in life activities despite pain and sleep symptoms were also associated with long-term improvements in insomnia, but willingness to experience sleep and pain symptoms were not contributing factors. Support (if any): This work was supported by PHS grant 5R01AG053221.